Simplification of the Bielchowsky head tilt test for the general practitioner - Lapierre, Nicole (Canadian Journal of Optometry, 1982)
The following is a short, but nonetheless important idea in orthoptics. It has the potential of not only facilitating a difficult part of exam questioning but also of simplifying an examination technique for the practitioner.